Projeto de antena de microfita dualband aplicada a veículos aéreos não tripulados - Medeiros, Isaac Marcelino de (Universidade Federal Rural do Semi-Árido, 2018)
With the advancement of technologies, new gadgets have come up with time. Many of these mechanisms are created to help and facilitate human life, so they need to be controlled. In the case of wireless systems, the reception or transmission of data and commands is carried out by sets of antennas, which in many cases must be reduced, have a good flexibility among other necessary parameters, thus appearing microfita antennas, have small dimensions and are used in low frequency, being widely used in the telecommunications area. This work aims to design a multiband antenna to be implemented in the VANT. The antenna design starts from the definition of the required frequency characteristics, thus choosing the type and geometry of the antenna to meet these requirements. The HFSS software was used in order to simulate and obtain the computational results. In this way, it was possible to find an antenna structure that best suited the frequency of 2.4 GHz and 5.8 GHz, thus achieving the practical test and the elaboration of antennas. Based on all the theoretical knowledge made at work it was possible to construct the antennas and check their dual band behavior.
Monografia
Keywords: Antena de Microfita; VANT; Dual Band Antenas; Microfite Antenna; VANT; Dual Band Antennas; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA